First report of Enterobacter cloacae as a causative agent of soft rot disease in dragon fruit (Hylocereus undatus) stems in Peru - Soto, J. (2019)
The objective of the present research was to identify the causal agent of soft rot disease in the stems of pitahaya plants (Hylocereus undatus (Haw.) Britton & Rose), also known as dragon fruit, in two production areas of Peru. Typical symptoms observed include rotting and soft consistency in stems, as well as yellowish colourations, which usually begin at the tips and outer edges of the stems and extend until they are completely decomposed. Symptomatic samples of pitahaya stalks were collected from two commercial fields, the first from the district of Independencia, Pisco, Ica, and the second from the district of Naranjos, Rioja, San Martin. The collected samples were transferred to the phytopathology laboratory of the National Agrarian University – La Molina where 19 bacterial colonies isolated from symptomatic stem tissue were processed. Nine bacterial colonies were selected from the initial 19 for further analysis. The nine selected colonies were gram negative, positive for the catalase enzyme, negative for the enzyme oxidase, and positive for pectinase production, which causes soft rot in potato tubers. These results indicated that these isolates correspond to the Enterobacteriaceae family. According to molecular tests and analysis of the 16s region of ribosomal DNA, all bacteria corresponded to a single taxonomic genus, Enterobacter. This bacterium presented a 99.85% homology with Enterobacter cloacae (accession number MH788982.1). The sequences from the nine selected isolates were entered into GenBank under accession number MN784371. In the pathogenicity test, 100% infection was obtained in the pitahaya stems and plants inoculated with E. cloacae, and the symptomatology that developed was the same as that observed in the two fields from where the samples were collected. Given these results, it can be concluded that E. cloacae is a causative agent of soft rot disease of the stems of H. undatus in the districts of Independencia and Naranjos, and this is also the first report of this bacterium as a pathogen of pitahaya in Peru.